Kompetensi Pembimbing Klinik dan Perilaku Caring Mahasiswa Keperawatan - Tri Widiyaningsih; Lilis Yunita; Iswanti Mediyani (FORIKES, 2023)
Caring behavior is inherent in every nursing student. Nursing students are professionally trained to develop caring behavior through the concept of clinical supervisor role models. The purpose of this study was to analyze the relationship between the competence of clinical supervisors and the caring behavior of nursing students. This quantitative research design was cross-sectional. The sample in this study were 160 diploma III nursing students who were selected by purposive sampling technique. Clinical supervisor competence and caring behavior of nursing students were measured by filling out a questionnaire. Data were analyzed using the Chi-square test. The results of the analysis show the value of p = 0.000. Furthermore, it was concluded that the competence of clinical supervisors was significantly related to the caring behavior of nursing students. This proves that the competence of clinical supervisors influences the formation of nursing student caring behavior.Keywords: competence of clinical supervisors; caring behavior; student of nursing ABSTRAK Perilaku caring melekat dalam diri setiap mahasiswa keperawatan. Mahasiswa keperawatan dilatih secara profesional untuk mengembangkan perilaku caring melalui konsep role model pembimbing klinik. Tujuan penelitian ini adalah untuk menganalisis hubungan antara kompetensi pembimbing klinik dengan perilaku caring mahasiswa keperawatan. Rancangan penelitian kuantitatif ini adalah cross-sectional. Sampel pada penelitian ini yaitu 160 mahasiswa diploma III keperawatan yang dipilih dengan teknik purposive sampling. Kompetensi pembimbing klinik dan perilaku caring mahasiswa keperawatan diukur melalui pengisian kuesioner. Data dianalisis menggunakan uji Chi-square. Hasil analisis menunjukkan nilai p = 0,000. Selanjutnya disimpulkan bahwa kompetensi pembimbing klinik berhubungan secara signifikan dengan perilaku caring mahasiswa keperawatan. Hal tersebut membuktikan bahwa kompetensi pembimbing klinik mempengaruhi pembentukan perilaku caring mahasiswa keperawatan.Kata kunci: kompetensi pembimbing klinik; perilaku caring; mahasiswa keperawatan